Valorização dos saberes astronômicos de uma aldeia indígena Terena no Estado de São Paulo - Ortiz, Marisa Serrano [UNESP] (2014)
Currently, with the process of acculturation and the increasing urbanization of the indigenous population in the country, as there is a number of this population living outside the villages or in villages very close to urban centers, there is evidence of a legitimate concern for the preservation of the cultural identity of these people. Thus, the Education for Science appears as one of the most important aspects to intervene in this process. In this scenario this research ais at a re-approachment of Terena indigenous community to the Knowledge of astronomy. The perspective is to promote and enhance the knowledge and view of the sky using a researcher as a mediator who recorded the experience by developing an instructional notebook with the participation of the community. With the purpose of unlocking the curiosity and grasp concepts relating them to the universe of expecatations and use in everyday life, we constructed a timer from the sun, and also we developed diversified activities of skywatching. A qualitative methodology was guided by theoretical substantion of authors from the fields of Education, Culture and Indigenous Astronomy. Based on this study it is expected that the teaching of indigenous astronomy has the role to contribute to the reflection and subsequence applications of situations of teaching/learning that can reaffirm ethnic identities, valuing the languages and science as well as ensuring access of the community to information and astronomical knowledge with the understanding that these acquisitions become appropriations consistent with indigenous values. Only with respect to these different ethinic groups the culture, beliefs and rights will be preserved